Review on the Relationship between Human Polyomaviruses-Associated Tumors and Host Immune System - Serena Delbue; Manola Comar; Pasquale Ferrante (Clinical and Developmental Immunology)
The polyomaviruses are small DNA viruses that can establish latency in the human host. The name polyomavirus is derived from the Greek roots poly-, which means “many,” and -oma, which means “tumours.” These viruses were originally isolated in mouse (mPyV) and in monkey (SV40). In 1971, the first human polyomaviruses BK and JC were isolated and subsequently demonstrated to be ubiquitous in the human population. To date, at least nine members of the Polyomaviridae family have been identified, some of them playing an etiological role in malignancies in immunosuppressed patients. Here, we describe the biology of human polyomaviruses, their nonmalignant and malignant potentials ability, and their relationship with the host immune response.